(untitled) (Journal of Partial Differential Equations, 1995)
In this paper we consider the Cauchy problem and the initial boundary value (IBV) problem for the inhomogeneous GBBM equations. For any bounded or unbounded smooth domain, the existence and uniqueness of global strong solution for the Cauchy problem and IBV problem for the inhomogeneous GBBM equations in W^2,p(Ω) are established by using Banach fixed point theorem and some a priori estimates. These results have improved the known results even in the case of GBBM equation. Meanwhile, we also discuss the regularity of the Strong solution and the system of inhomogeneous GBBM equations.